The time course of syllable frequency effects in the visual recognition of Korean morphologically complex nouns: an ERP study - Kwon, Seoyeon; Lee, Solbin; Kim, Joonwoo; Nam, Kichun (Frontiers in Language Sciences, 2024)
The syllable frequency effect refers to that during the lexical decision task, words beginning with high-frequency syllables elicit slower responses than words beginning with low-frequency ones, indicating an inhibitory effect. However, previous studies in Korean have yielded mixed results. For morphologically simple words, an inhibitory or null effect has been observed, while for morphologically complex words, a facilitative effect has been reported, though the explanations for these findings remain unclear. This study employed both behavioral and electrophysiological methods to investigate the temporal dynamics of the facilitative syllable frequency effect in Korean morphologically complex nouns. A secondary aim was to explore whether syllable frequency is modulated by stem length as a factor in morphological processing, at both the behavioral and neurophysiological levels. The behavioral data showed that lexical decision latencies were faster for morphologically complex nouns with higher syllable frequencies compared to those with lower frequencies. The ERP data revealed a significant syllable frequency effect on the P300 component, reflecting early visual word processing. However, no significant effect was found in the N400 component. While stem length did not significantly influence behavioral results, it did show significant differences in N250 amplitudes. Notably, an interaction between syllable frequency and stem length had a significant effect on N400, in contrast to the behavioral findings. The findings suggest that, in the processing of morphologically complex words in Korean, syllable frequency serves as partial information that facilitates lexical decisions through the fast-guess mechanism, as proposed by the MROM-S model and the delayed time window for syllable processing may stemmed from a different stage of the processing between morphologically complex words and morphologically simple words. Furthermore, stem length, as a form of morphological processing, may interact with syllable frequency during the lexical access stage.